Early Life Nutrient Restriction Impairs Blood-Brain Metabolic Profile and Neurobehavior Predisposing to Alzheimer’s disease with Aging - Tomi, Masatoshi (2012)
Prenatal nutrient restriction (NR) culminating in intra-uterine growth restriction (IUGR) with postnatal catch up growth leads to diabesity. In contrast, postnatal NR with growth restriction (PNGR) superimposed on IUGR (IPGR) protects young and aging adults from this phenotype. We hypothesized that PNGR/IPGR will compromise the blood-brain metabolic profile impairing neurobehavior and predisposing to Alzheimer’s disease (AD). NR (50%) in late gestation followed by cross-fostering of rat pups to either ad lib fed (CON) or NR (50%) lactating mothers generated CON, IUGR, PNGR and IPGR male (M) and female (F) offspring that were examined through the life span. In PNGR/IPGR plasma/CSF glucose and lactate decreased while ketones increased in (M) and (F) (PN21, PN50). In addition increased brain glucose transporters, Glut1 & Glut3, greater brain derived neurotrophic factor (BDNF), reduced Glut4, with unchanged serotonin transporter concentrations were noted in (F) (PN50-60). While (F) displayed more hyperactivity, both (F) and (M) exhibited anxiety although socially and cognitively unimpaired (PN25-28&50). Aging (15-17m) (F) not (M), expressed low plasma insulin, reduced brain IRS-2, pAkt, and pGSK-3p(Ser9), unchanged pPDK1, pTau or lipoprotein receptor related protein 1 (LRP1), higher glial fibrillary acidic protein (GFAP) and spinophilin but a 10-fold increased amyloid-p42. We conclude that therapeutically superimposing PNGR on IUGR (IPGR) should be carefully weighed in light of unintended consequences related to perturbed neurobehavior and potential predilection for AD.